Factors Affecting Customer Loyalty of Bank Syariah Indonesia - Muhammad Agus Supriyanto; Siswanto; Yayuk Sri Rahayu (Universitas Pendidikan Ganesha, 2023)
This study aims to analyze the factors that influence customer loyalty at Bank Syariah Indonesia. The study used five hypotheses and examined the relationship between service quality, customer satisfaction, religiosity, and customer loyalty. This study used quantitative data with descriptive methods. The population used in this study is all customers of Bank Syariah Indonesia. The study samples amounted to 158 samples taken using non-probability sampling techniques. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results showed that service quality has a significant direct influence on customer satisfaction. Customer satisfaction also has a significant direct influence on customer loyalty. Religiosity cannot moderate service quality in influencing customer satisfaction. This research contributes to Bank Syariah Indonesia in developing more effective marketing strategies and strengthening relationships with customers. This study also provides a theoretical contribution by examining the relationship between factors that influence customer loyalty at Bank Syariah Indonesia. Future research may consider other variables that may affect customer loyalty, such as value perception and brand image.